Capstone and Cornerstone: Creating a Virtual Research Centre in Honours and Graduate Courses in Renaissance Literature - Popham, Elizabeth (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (Iter Press, 2014)
For the past three years, I have experimented with courses for senior undergraduate and first year graduate students that incorporate features of directed reading projects, making use of a Managed Learning System (MLS) site as a “virtual research centre” for collaborative investigation of critical issues in the reading of Elizabethan texts. An honours seminar on “Sex and Politics in Elizabethan England” provided a “capstone” experience for fifteen students conducting independent research projects on a group of core texts. Research logs were posted on “Themes and Issues” pages, and essays were published in a journal on the MLS site. In master’s-level classes on “The Life-Cycle of Some Renaissance Texts,” a similar system provided a “cornerstone” for graduate studies. Each student adopted a text that presented issues related to publication, authorship, circulation, or historical “afterlife.” Work-in-progress was shared in class and on the MLS site, and the group acted as the editorial committee for an online journal.